EFEK SALINITAS RENDAH TERHADAP TINGKAT KERJA OSMOTIK DAN PERTUMBUHAN UDANG WINDU (Penaeus monodon Fab) - Muslim Muslim (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2003)
For a long time fish farmers used mangrove and marginal area of low salinity for tiger prawn (Penaeus monodon Fab) pond culture. The objective of this study was to know osmotic work level and growth of tiger prawn stocked in low salinity medium. Study carried out from may to July 2001 at the Aquaculture Laboratory, Department of Fishery, Fishery and Marine Science. Faculty, Diponegoro University Semarang. Study was performed with laboratory experiment, in which 4 salinity levels treatment and 3 replications were administered. The treatment was A (2%), B (6%), C (10%), and D (15%). Twelve buckets with the volume of 35 l each were used as the medium. Four tiger prawns with individual weight ranged from 2,48g to 2,60g were stocked in each of bucket. Osmotic work level growth of tiger prawns and water quality during the experiment were used as indicators the effect of different levels salinity. The result of study revealved that osmotic work level at the premolt phase in treatment A,B, C and D was 528.55, 528.41, 566.32, and 130.69mOsm/H2O respectively. At the molt phase, it was 786.33, 574.61,559,40 and 124.73 mOsm/l H2O respectively, and at the intermolt phase it was 528.93, 425.08, 330.35 and 127.25 mOsm/l H2O respectively. Growth of the prawn in the treatment A,B,C, and D was 0,30 , 0,47 , 0,48 , and 0,56 g respectively. The study recorded increasing osmotic work level and descreasing growth of tiger prawns along with decreasing salinity levels. Keywords : salinity, osmotic, growth, tiger prawn